Legitimacy and competitiveness of electronic scientific periodicals of Ukraine approved for publication of dissertation results. - Dzyak, G. V.; Pototskaya, O. Yu. (Морфологія / Morphologia / Morfologìâ, 2013)
Electronic media become more and more popular throughout the world, especially in the field of science. Numerous benefits of electronic scientific journals comparing with the printing ones make them more attractive for readers and libraries. Despite the world tendency in shifting from print to electronic-only scientific journals, Ukrainian legal system restricts possibilities of e-journals in publishing results of scientific works. Concerning possible reasons of such restrictions we revealed that the only unresolved problem is the absence of proper legal regulation of the process of state registration. The National Register of electronic information resources was created several years ago, but the requirement to register scientific periodical e-journals on this site is absent. Meanwhile editorial board and editors can voluntary register electronic issues by their own initiative. In this way electronic journals will equalize with the print ones in their legal status, so the mentioned restrictions in their rights need to be removed. To improve confidence in the long-term preservation of materials published in electronic journals editors need to be encouraged to subscribe their issues in the system of digital object identifier. As e-only journals are more financially profitable, government need to stimulate publishers to use this model instead of/in parallel with the print one. To make this transition possible, libraries should be supplied with proper equipment and personnel.